2003
DOI: 10.1093/jn/133.7.2268
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols Decrease Plasma Triglycerides and Cholesterol Accumulation in the Aorta of Ovariectomized Guinea Pigs

Abstract: Female ovariectomized guinea pigs, a model for menopausal women, were fed either a control diet or a diet containing 10 g/100 g of a lyophilized grape preparation for 12 wk. The macronutrient composition of the grape preparation was: simple carbohydrates, 90 g/100 g; protein, 4 g/100 g; and dietary fiber, 6 g/100 g. Control and grape diets had the same composition except for the percentage of macronutrients provided by the grape preparation. Polyphenols were present in the grape preparation at 0.58 g/100 g and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 31 publications
7
75
0
4
Order By: Relevance
“…According to the manufacturer's data sheet, GSE used in the present study contains polyphenols. It was reported that polyphenols can decrease TG concentration in the blood of rats and guinea pigs by changing lipid metabolism in the liver (Aprikian et al, 2003;Zern et al, 2003;Nakamura and Tonogai, 2002). Therefore, the decreased TG concentrations observed in the present study might not be a toxicological change but rather an effect due to polyphenols in GSE.…”
Section: Discussionmentioning
confidence: 45%
“…According to the manufacturer's data sheet, GSE used in the present study contains polyphenols. It was reported that polyphenols can decrease TG concentration in the blood of rats and guinea pigs by changing lipid metabolism in the liver (Aprikian et al, 2003;Zern et al, 2003;Nakamura and Tonogai, 2002). Therefore, the decreased TG concentrations observed in the present study might not be a toxicological change but rather an effect due to polyphenols in GSE.…”
Section: Discussionmentioning
confidence: 45%
“…In the case of LDL-cholesterol, significant reductions have been observed in studies in both animals (13,27) and in human subjects (24,29,33,65,68,69) , although other studies have reported no effect either in animals (11,70) or in human subjects (21,24,47,66,67) .…”
Section: Total Cholesterol Ldl-cholesterol and Hdl-cholesterolmentioning
confidence: 99%
“…The duration of Table 1. Main compositional characteristics of grapes and polyphenol-rich derived products (9,14,28,30,34) (11) Twenty-three ovariectomised guinea-pigs 12 weeks Control treatment or diet with 10 % freeze-dried grapes, 6 % dietary fibre and 0·5 % total polyphenols. Intake ad libitum Ruf et al (1995) (12) 144 rats 4 months Series 1: tap water, ethanol 6 %, red wine diluted in water (6 % ethanol) or white wine diluted in water (6 % ethanol) Series 2: ethanol 6 %, red wine diluted in water (6 % ethanol), ethanol 6 % with 0·2 % glycerol or ethanol 6 % with 0·025 % grape seed extract Series 3: ethanol 6 %, red wine diluted in water (6 % ethanol) or red wine extract added to ethanol 6 % Series 4: water, red wine diluted in water (6 % ethanol) with the same content in glycerol as dealcoholised red wine or dealcoholised red wine Martín-Carró n et al (2000) (13) Twenty-four rats 4 weeks Diet with and without cholesterol, two groups in each: control treatment or product from grapes rich in polyphenols (1·63 %) and fibre (50 %) (10 % diet) Martín-Carró n et al (2000) (13) Eighty rats 42 d Diet with and without cholesterol, three groups in each: control with cellulose, white grape peel or white grape seed (all the groups with 54-59 % dietary fibre) Falchi et al (2006) (14) Rats 30 d Grape seed extract (0·18-0·33 % total polyphenols fresh matter), grape flesh extract (0·03 -0·04 % total polyphenols fresh matter) or water Osman et al (1998) (22) Five (26) Eighty rats 10 weeks Diet with cholesterol supplemented with: cellulose, grape pomace, apple pomace or tomato pomace Diebolt et al (2001) (40) Twenty-four rats 1 week Product with glucose 5 % or two different extracts of polyphenols from red wine (in all cases, 20 mg/kg weight per d) Bernatova et al (2002) (41) Forty-eight rats After taking L-NAME for 3 weeks, three groups:…”
Section: Introductionmentioning
confidence: 99%
“…Puglisi et al [45] found that using one cup of raisins per day for 2 weeks in humans significantly decreased total cholesterol, triglycerides and LDL. This hypolipidaemic effect of raisins might be due to polyphenols content interference with cholesterol absorption [60] and decrease of hepatic cholesterol concentrations as observed in guinea pigs [61] after diet supplementation with lyophilised grape powder. Similarly, the hypocholesterolaemic effects of raisins were proven by Spiller et al [51].…”
Section: Discussionmentioning
confidence: 99%